Rainfall changes over tropical montane cloud forests of southern Western Ghats, India - Murugan, Muthusamy; Shetty, Paddu Krishnappa; Anandhi, Aavudai; Ravi, Raju; Alappan, Subbiah; Vasudevan, Muhund; Gopalan, Sreeja (My University, 2013)
The southern Western Ghats tropical montane cloud forest sites (Gavi, Periyar, High wavys and Venniyar), which are characterized by frequent or seasonal cloud cover at the vegetation level, are considered one of the most threatened ecosystems in India and the world. Three out of four montane cloud forest sites studied in the southern Western Ghat had experienced diminishing trends of seasonal average and total rainfall, especially during summer monsoon season. The highest level of reduction for summer monsoon season was observed at Gavi rainforest station (>20 mm/14 years) in Kerala followed by Venniyar (>20 mm/20 years) site in Tamil Nadu. Average annual and total precipitation increased during the study period irrespective of the seasons over Periyar area, and the greatest values were recorded for season 2 (>25 mm/28 years). Positive trends for winter monsoon rainfall has been observed for three stations (Periyar, High wavys and Venniyar) except Gavi, and the trend was positive and significant (90%) for Periyar and High wavys. Increase in summer monsoon rainfall was observed for Periyar site and the trend was found to be significant (95%).
Citation: Murugan, M., Shetty, P., Anandhi, A., Vasudevan, M., & Gopalan, S. (2009). Rainfall changes over tropical montane cloud forests of southern Western Ghats. Current Science, 97(12), 1755-1760.
Keywords: Meghamalai; Montane cloud forest; Precipitation change